The Proposed Model of Suppliers Performance Measurement for Vendor Held Stock (VHS) in Mining Industry - Sri Wahyuni; Suparno Suparno; Iwan Vanany (Institut Teknologi Sepuluh Nopember, 2020)
Vendor Held Stock (VHS) is the storage and management a system for spare parts and other material must prepared and managed with the suppliers in case study. The case study in this research is in nickel mining company in Indonesia. The company’s case study requires all suppliers should provide the spare parts and other materials in their warehouses. The purpose of this study is to develop VHS supplier’s performance measurement system in case study. The key performance indicators (KPI’s) in VHS’s supplier performance measurement system are determined to ensure the buyer demand can be fulfilled in a timely, systematic and well organized with the correct quantity and maintained quality. The method used in measuring supplier performance is a combination of the Analytical Hierarchy Process (AHP), The Objective Matrix (OMAX) and Fishbone Diagram Methods. The results of this research are expected to obtain measurement models and find the root cause and solutions to the current problem to improve overall supplier performance.